Dancing Is Only Part of the Job: An Immersive Course in Dance Entrepreneurship. Issue 2 (3rd April 2019) - T'ai, Gina
ABSTRACT: This article details my journey in teaching the college course Topics in Dance Entrepreneurship in the spring of 2017. The students, with my support, built a performing dance collective from the ground up. They learned how to self-produce, create a mission statement, work with producing partners, curate and learn repertory, and work in the community, giving performances to populations of all ages. In a nutshell, the course prepared the dancers for work they will encounter outside of the studio and classroom environment, giving them real-world experiences.